Conventional supportive cancer care services in Australia: A national service mapping study (The CIA study). Issue 3 (13th March 2021) - Pinkham, Elizabeth P.; Teleni, Laisa; Nixon, Jodie L.; McKinnel, Emma; Brown, Bena; Joseph, Ria; Wishart, Laurelie R.; Miller, Elizabeth; Ward, Elizabeth C.; Hart, Nicolas H.; Lock, Gemma; Hanley, Brigid; et al.
Abstract: Aim: Cancer and its treatment produce significant acute and long‐term adverse effects in cancer survivors, resulting in a range of supportive cancer care needs across the disease trajectory. To enhance supportive cancer care in Australia, this study sought to understand and describe conventional services offered nationwide, specific to their structure (ownership, setting, duration), process (participants, delivery mode, referral pathways), and outcomes (evaluation). Methods: A survey canvassing 13 conventional supportive cancer care interventions was electronically distributed to 265 cancer organizations in all Australian states and territories over 2019 and 2020. Cancer organizations were invited to participate if they provided at least one cancer‐directed treatment (ie, surgery, radiation therapy, or systemic therapies); or clinical cancer care to adults, adolescents, or children; or conventional supportive care interventions to cancer survivors. Results: A response rate of 46% (n = 123/265) was achieved, with 72% of cancer organizations (n = 88) delivering at least one intervention. Most were provided as outpatient or inpatient services, with few at home (<13%) or via telehealth (<10%). Psychological therapy (90%), self‐care (82%), exercise (77%), healthy eating (69%), and lymphedema (69%) services were most common. Fatigue management (51%) and pelvic health (32%) were less common. Services offering massage, return‐to‐work, cognitive therapy, sleep hygiene, and leisure were underrepresented (<31%). Conclusion: Provision of conventional supportive cancer care services continues to evolve in Australia. Multiple areas of care require development of dedicated services to address supportive cancer care intervention shortfalls across the country. Online resources and telemedicine are currently underutilized modalities that are available for further development. Abstract : This national survey is the first to summarize the contextual domains of supportive cancer care (SCC) interventions in Australia, identifying low numbers of some key SCC interventions and the limited availability for most interventions beyond 5 years. Our study highlights the need for future research on the implementation strategies of SCC interventions across modes of delivery and settings.